Care of Neonates and Children During Corona Crisis and Importance of Continuation of Essential Services - Rahat, Farhana; Choudhury, Ahmed Murtaza (Dhaka Shishu (Children) Hospital Journal, 2022)
The corona virus disease (SARS-CoV-2) has rapidly spread across the world and global population including children are facing unprecedented health crisis. The chance of vertical and perinatal transmission of SARS-CoV-2 virus in children is not proven yet. The effect of the virus on neonate and infant appears to be small. On the other hand, pregnant women suffering from corona virus disease may give birth to premature or IUGR babies who will need extra care. Breast feeding is considered as gold standard in almost all situation. Continuation of breast feeding along with other essential services have reduced the risk of transmission of corona virus. DS (Child) H J 2021; 37(1): 5-8